Analisis Kualitas Produk Dan Branding “J-Connect” Terhadap Kepuasan Dan Loyalitas Nasabah Bank Jatim Di Area Pemasaran Wilayah Kediri - Wahyu Krisna Junaidhy; Arisyahidin Arisyahidin; Sonny SM Laksono (Otonomi, 2023)
The increasing need for life causes people to make multipurpose credit as an alternative choice in dealing with this. This of course causes the banking world to offer various facilities for the public in accessing this matter, Bank Jatim is no exception. Bamk Jatim as BPD offers various facilities for the public in accessing its products, including multipurpose loans. This is the basis for researchers to find out that Bank Jatim creates product attributes so that it can compete and survive until now. The purpose of this study is to analyze the effect of product quality and brand image on consumer satisfaction, the effect of product quality and brand image on customer loyalty, analyze the effect of consumer satisfaction on customer loyalty, and analyze the effect of product quality and brand image on customer loyalty through customer satisfaction. This research was conducted at the Jatim bank in the marketing area of ​​the city of Kediri. The sampling method is the non-probability sampling method with the provision of samples that must be carried out by East Java bank consumers who borrow at least 2 times and when the respondents are carried out using Wibisono (2003) calculations and obtained the number of respondents as many as 96 people. In this study, the primary data collection method was obtained through interviews using questionnaires and documentation. Secondary data collection is obtained through documentation by recording documents obtained from relevant agencies related to research purposes and collecting data from related literature or libraries. The data analysis method used in this study is path analysis, which is to see the path of influence that occurs between the variabels of consumer satisfaction and brand image on consumer satisfaction and customer loyalty. The results showed that product quality and brand image had a significant effect on consumer satisfaction by 10.76% and 14.75%, respectively.